Tomorrow's In-Car Interconnect? : A Competitive Evaluation of IEEE 802.1 AVB and Time-Triggered Ethernet (AS6802) - Till Steinbach and Hyung-Taek Lim and Franz Korf and Thomas C. Schmidt and Daniel Herrscher and Adam Wolisz (IEEE, 2012)
Ethernet-based in-car communication is currently a hot topic in the automotive industry. Soon Ethernet will start to oust MOST bus in its domain of info- and entertainment applications. However, the full benefit of a technologically integrated in-car network will only become rewarding with the deployment of an Ethernet-based backbone that integrates all automotive domains on a single layer at increased bandwidth, reduced complexity and cost, while opening car intelligence for future innovations. Such backbone must transport critical control data in real-time. Standard Ethernet requires extensions to comply to the strict timing requirements of driver assistance and safety applications while simultaneously supporting broadband multimedia traffic. In this paper, we compare IEEE 802.1 AVB and Time-triggered Ethernet, two competing real-time approaches. While the first fosters over-provisioning and prioritisation, the second is based on a \em coordinated time-division-multiple-access (TDMA) policy for media access. By simulating a realistic in-car backbone design and traffic model, we reveal the strengths and weaknesses of both protocols and point to the diverging characteristics of event- and time-triggered policies. Our results show that in this in-car network scenario both protocols are able to meet the rigid timing requirements, while each has its unique benefits and disadvantages.